Autómatas programables y su influencia en la educación académica de los estudiantes del área de electricidad, Colegio Fiscal Simón Bolívar de la ciudad de Guayaquil - Muñoz Zea, Felipe Antonio (2019)
The programming instruments and electrical automations are classified according to their specific functions. With the advance of science and technology, new equipment and instruments for informational data processing have emerged in the international or worldwide market, which is extremely important to meet the needs in the control of industrial processes, from the technological point of view the equipment Currently, programmable automations have widely gained ground in the industrial technical area, which provides the operator with the appropriate instructions in order to visualize, monitor the condition, conditions and operation of electric machines. Currently, the basic and fundamental components that usually constitute the Programmable Automata are: electrical, electromechanical and electronic, for their correct operation. The fundamental and important aspects that programmable automation equipment possesses are those manual programming equipment and instruments and at the same time they are versatile of smaller size, it does not require much space, its installation is simple according to the instructions, characteristics and technical specifications. With regard to their importance, they allow us to save considerably the cost of the supply of electrical energy, as well as adequately perform the control and control of electrical machines. The Technical Teaching of Programmable Automata for the Academic Education of the students directly influence the technique of use, assembly, operation, installation, connection, wiring, programming, information processing and operation, considering the continuous use of the instructions, application of concepts, characteristics and technical specifications in order to provide basic knowledge in the Teaching - Learning process.